Pengaruh Pengalaman Konsumen dan Reputasi Perusahaan Terhadap Kepuasan Konsumen dan Loyalitas Konsumen - Sholekhatun Nisa; Lia Amalia; Nina Nurhasanah; Elistia Elistia (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The high growth of the cosmetics industry also creates problems in the form of business competition between companies and marketers operating in the cosmetics industry. This creates opportunities for the Indonesian cosmetics industry, with many new products entering the market, resulting in very tight competition. This provides opportunities for the cosmetics industry in Indonesia, so that many new products appear on the market which creates quite tight competition. This research aims to determine the influence of consumer experience and company reputation on consumer satisfaction and consumer loyalty. The research method uses descriptive causality in this study the population studied is those who have used Maybelline at least 2 times in the Kebon jeruk area. The sample in this study amounted to 180 respondents using the structural equation model (SEM) method. Based on the test results, it is known that consumer experience has a positive effect on consumer loyalty and consumer satisfaction has a positive effect on consumer loyalty. Consumer experience and company reputation have no effect on consumer satisfaction. Company reputation has no influence on consumer loyalty.